Collages of Memory: Remembering the Second World War Differently as the Epistemology of Crafting Cultural Conflicts between Russia and Ukraine. Issue 4 (3rd July 2016) - Khrebtan-Hörhager, Julia
Abstract: This essay critically examines the current duality of Russian-Ukrainian intercultural relations and explores the subject of politics of active and selective memory as the claimed root of current controversies and military tensions. Through rhetorical analysis of historical and contemporary national narratives, it demonstrates how culturally defining experience of the Second World War and the Great Patriotic War is remembered, rethought, and reused by respective parties to reinvent the Self and the Br/Other, as well as rethink ones positionality on the world arena.